Free testosterone/cortisol ratio in soccer: usefulness of a categorization of values - Banfi, G.; Dolci, A. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: The free testosterone:cortisol ratio (FTCR) is widely used for studying and preventing overtraining syndrome in various sports. The use of FTCR for following overtraining syndrome was proposed originally with two approaches: FTCR lower than 0.35¥10-3, calculated on free testosterone (FT) in nanomoles per liter (nmol/L) and on cortisol (C) in micromoles per liter (mmole/L) or a decrease of the ratio of 30% or more in comparison with the previous value. In our experience, the use of an absolute value as a threshold is not useful, whereas the evaluation of the concentrations of hormones and their ratio in comparison with previous ones is more useful. These classical approaches are not, however, sufficient to describe the various possible physiological modifications linked to training excess and/or incomplete recovery. Methods: We collected samples from 32 professional soccer players of an Italian First Division team, during the period July 2001-July 2003. We analyzed the values of 21 athletes during the season 2001-2002 and of 11 athletes during the season 2002-2003 (6 out of 11 were examined also during the previous one) always present when the 4 (first season) or 5 (second season) blood drawings have been performed. We applied an original, pragmatic and easy-to-use classification of FTCR values, in association with classical interpretations based on decreases of the values in comparison with previous athlete's result. Results: We used the traditional approaches in two consecutive seasons in a professional soccer team: the evaluation of the decrease >30% of the parameter in comparison with the previous value or with the basal (preseason) value are shown. The statistical differences between the FTCR values of the six athletes followed in both seasons were not significant. Conclusions: The classification method we propose is advantageous in comparison with traditional interpretative schemes, because identify different risk categories, stratifying the interval between the values 0.35-0.8.